Sperm forward motility is negatively affected by short‐term exposure to altitude hypoxia. (14th January 2016) - Verratti, V.; Di Giulio, C.; D'Angeli, A.; Tafuri, A.; Francavilla, S.; Pelliccione, F.
Summary: Human exposure to altitude is a model to study the role of oxygen in different areas of physiology and pathophysiology. The aim of this study was to evaluate whether a short exposure to hypoxia (5 days) combined with exercise, at altitude ranging from 900 m above sea level to 5895 m above sea level (Kilimanjaro Expedition) can modify seminal and reproductive hormonal parameter levels in human beings. During the ascent, blood oxygen saturation at 3.848 m above sea level was found to be decreased when compared to sea level ( P < 0.02). The sperm forward motility at sea level after the expedition showed a significant reduction ​​( P < 0.02). There were no changes in other seminal parameters among those compared. Determination of the hormonal plasma concentrations showed that baseline values of follicle‐stimulating hormone, total testosterone, prolactin and oestradiol were unchanged at sea level after the hypoxic experience, with respect to baseline values at sea level. On the other hand, luteinising hormone levels after altitudes trekking significantly increased compared to levels before the expedition ( P < 0.05). Because of the short‐term exposure, we can assume that the reduced forward motility described here may result from the effects of the acute altitude hypoxia on spermatozoa during the epididymal transit where they mature acquiring their motility.